2009 11th International Conference on Computer Modelling and Simulation 2009
DOI: 10.1109/uksim.2009.21
|View full text |Cite
|
Sign up to set email alerts
|

Support Vector Machines for Anatomical Joint Constraint Modelling

Abstract: Abstract-The accurate simulation of anatomical joint models is becoming increasingly important for both realistic animation and diagnostic medical applications. Recent models have exploited unit quaternions to eliminate singularities when modeling orientations between limbs at a joint. This has led to the development of quaternion based joint constraint validation and correction methods. In this paper a novel method for implicitly modeling unit quaternion joint constraints using Support Vector Machines (SVMs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Due to inaccuracy in the neural network some correction of valid orientations takes place. Research has shown that an SVM classifier can be used to separate valid orientations from those requiring correction [29]. Recent research [30] has looked employ unsupervised learning more applicable to use with recorded actor or patient specific data (such as that gathered by Herda, Urtasun and Fua [26]).…”
Section: Related Workmentioning
confidence: 99%
“…Due to inaccuracy in the neural network some correction of valid orientations takes place. Research has shown that an SVM classifier can be used to separate valid orientations from those requiring correction [29]. Recent research [30] has looked employ unsupervised learning more applicable to use with recorded actor or patient specific data (such as that gathered by Herda, Urtasun and Fua [26]).…”
Section: Related Workmentioning
confidence: 99%